Linguistic analysis of gender asymmetry in courtroom interaction discourse. Analysis of questioning strategies in domestic violence trials in Italy - Novella Benedetti (Pragmalingüística, 2024)
The article conducts an exploratory analysis of questioning strategies in Italian trials of domestic violence cases. The aim is to compare the questioning of complainants (survivors) and defendants (alleged aggressors) to determine whether gender asymmetry exists (i.e., differences in the treatment of complainants and defendants). The dataset collected includes three cases involving four hearings where complainants and four where defendants were witnesses. The analysis builds on Archer (2005) and Mortensen (2020) and is carried out through a quantitative (turn-taking, words spoken, average number of words per turn) and qualitative (morphosyntactic question types) analysis. Quantitative results show that complainants are asked more questions and can speak less in their answers. Regarding their morphological question types, in direct examination, high-control question types are asked more to defendants; in cross-examination, the opposite occurs. According to these findings, it may be said that a situation of gender asymmetry exists.